Peningkatan Hasil Belajar PPKn Materi Semangat Kebangkitan Nasional Melalui Model Game Based Learning Berbantuan Kahoot Pada Peserta Didik Kelas VIII F SMP Negeri 2 Mertoyudan Tahun Pelajaran 2021/2022 - Kulsum, Umi (Science and Education Journal (SICEDU), 2022)
The goals of this research are to describe the learning implementation process using the game-based learningtype helped by kahoot to increase the learning outcome of PPKn, to describe how much the increasing of the learning outcomes of PPKn after being given a used game-based learning model assisted by Kahoot, and to describe behavioral changes that accompany the improvement of PPKn learning outcomes National Awakening Spirit material by using a game-based learning model assisted by kahoot in class VIII F students of SMP Negeri 2 Mertoyudan in 2021/2022 school year. The method used is a classroom action research method which consists of two cycles. In the first and second cycles, learning is carried out using a game-based learning model with the help of Kahoot. Each cycle consists of planning, implementing actions, observing, and reflecting. The research subjects were 31 students, and the research data sources were obtained from qualitative data in the form of data from observations of teacher and student activities and quantitative data in the form of test data on student learning outcomes. The results of this study indicate that the use of game-based learning models assisted by kahoot can improve learning outcomes and changes in student behavior in class VIII F SMP Negeri 2 Mertoyudan for the 2021/2022 school year. In the pre-action, the number of students who achieved a score of 79 were 18 (58%) and <79 as many as 13 (42%) with an average grade of 76.45. In the first cycle test, the class average score was 81.61 students who scored 79 as many as 25 (80%) and <79 as many as 6 (20%), while in the second cycle the average score was 85.96 students who received the value of 79 is 31 (100%) and <79 is 0 (0%). Thus, the average value of students from pre-action to cycle I increased by 5.16 and from cycle I to cycle II also increased by 4.37. The increase in teacher activity in the first cycle was 56% and became 64% so that there was an increase of 8% as well as the activity of students, in the first cycle by 26% to 90% in the second cycle so that there was an increase of 64%.